(untitled) (Ustozlar uchun, 2025)
In recent years, Uzbekistan has undertaken comprehensive reforms in foreign language education across all levels of its educational system. The primary objective is to develop communicative competence in students, enabling them to operate effectively in multilingual and multicultural environments. At the preschool level, exposure to a foreign language builds foundational listening and speaking skills. In primary and secondary schools, the focus shifts to integrated curricula based on the Common European Framework of Reference for Languages (CEFR), communicative methods, and modern pedagogical technologies. At the tertiary level, foreign language instruction aims to support students’ academic and professional development, such as through English for Specific Purposes (ESP) and content-based learning. However, challenges remain, including teacher training, resource allocation, and consistent assessment practices. The evolution of the content reflects both national policy priorities and global trends, striving to balance linguistic, cultural, and functional competence.